The Rubberized Concrete For Crack Resistant Concrete Pavement - Ghasheir, Fouad M. Ali Bin; Setyawan, Ary; As’ad, Sholihin (Jurnal Teknik Sipil, 2014)
The concrete is the most used material in civil engineering world. The crumb rubber had been added to the concrete instead of fine aggregate to used in a walls as a sound insulator and less heat conduction compared with concrete without rubber. (Intesar et al, 2011). Many experiments were done to find out appropriate methods of rubber application. Commonly, fully replacing coarse aggregate (gravel) or fine aggregate (sand) with rubber is not appropriate because the loss of strength is too severe. However, with small portion of aggregates replaced, the loss in compressive strength was not significant. A research study by Khatib et al (1999) and Schimizze et al (1994) suggested that rubber should not exceed (17-20%) of the total aggregate volume. Whenever possible to use the waste tyres in the construction work, it is possible to find effective solutions to prevent environmental pollution. The aim of this research to investigate the property and crack resistant of rubberized concrete. This research used crumb rubber of waste tyres in a concrete as replacement of aggregate. Three dosage of crumb rubber (5,10 and 15)% by volume were used. One mixture of plain concrete was also tested as reference and compare the results to the standard specification of rigid pavement. Those mixtures then prepared for fresh concrete and hardened concrete test. Slump test was conducted for assessing the fresh concrete performance while for hardened concrete performance, the compressive strength at 3,14 and 28 days were tested, the restrained shrinkage for early age of concrete were tested for 6 hours from casting and the shrinkage measurements taken when the age of concrete 1,3,5,7,9,11,13,15,18,21,25, and 28 days. The results of this research show that the crumb rubber was an effective material to resist the cracks in concrete. The results of compressive strength show that the compressive strength decrease when the amount of crumb rubber increase. The results of shrinkage test and restrained shrinkage test show that the cracks in the concrete decrease when the amount of crumb rubber increase. The total crack length reduce by (18.6, 55.2 and 58.2%) when the aggregate was replaced by (5, 10 and 15%) of crumb rubber. The number of cracks reduce by (11.34, 42.67 and 49.34%) when the aggregate was replaced by (5, 10 and 15%) of crumb rubber. Keywords: crumb rubber, rubberized concrete, cracks, compressive strength, shrinkage, restrained shrinkage.